Inverted: A Screenplay Exploring Social Anxiety Disorder in Association with Online Dating Applications - Ivonia Winoto; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2023)
Online dating applications are one of the results of the advancement of technology and communication in the digital culture. The use of online dating applications, however, is bringing negative effects such as Social Anxiety Disorder or SAD to the users. SAD is known as a mental health problem that is marked by a persistent fear of being humiliated by others. One of the psychological effects of SAD is developing avoidance behavior which is marked by avoiding any social situations. This screenplay aims to explore how online dating applications may cause SAD, and how SAD will affect a person’s mental health condition to the extent that it will influence their relationship with others. This work is using Social Anxiety Disorder theory to analyze the link of the cause and effect of SAD with the dating applications. In results, this screenplay presents a link between SAD and online dating applications as there is trauma of rejection for the users which triggers the appearance of SAD. Also, the development of avoidance behavior is shown when a person with SAD avoids the feared situations completely.